Prevalence and Duration of Gastrointestinal Symptoms Before Diagnosis of Inflammatory Bowel Disease and Predictors of Timely Specialist Review: A Population-Based Study. (15th July 2020) - Blackwell, J; Saxena, S; Jayasooriya, N; Bottle, A; Petersen, I; Hotopf, M; Alexakis, C; Pollok, R C
Abstract: Background and Aims: Lack of timely referral and significant waits for specialist review amongst individuals with unresolved gastrointestinal [GI] symptoms can result in delayed diagnosis of inflammatory bowel disease [IBD]. Aims: To determine the frequency and duration of GI symptoms and predictors of timely specialist review before the diagnosis of both Crohn's disease [CD] and ulcerative colitis [UC]. Methods: This is a case control study of IBD matched 1:4 for age and sex to controls without IBD using the Clinical Practice Research Datalink from 1998 to 2016. Results: We identified 19 555 cases of IBD and 78 114 controls. One in four cases of IBD reported GI symptoms to their primary care physician more than 6 months before receiving a diagnosis. There was a significant excess prevalence of GI symptoms in each of the 10 years before IBD diagnosis. GI symptoms were reported by 9.6% and 10.4% at 5 years before CD and UC diagnosis respectively compared to 5.8% of controls. Amongst patients later diagnosed with IBD, <50% received specialist review within 18 months from presenting with chronic GI symptoms. Patients with a previous diagnosis of irritable bowel syndrome [IBS] or depression were less likely to receive timely specialist review (IBS: hazard ratio [HR] = 0.77, 95% confidence interval [CI] 0.60–0.99, depression: HR = 0.77, 95% CI 0.60–0.98). Conclusions: There is an excess of GI symptoms 5 years before diagnosis of IBD compared to the background population, probably attributable to undiagnosed disease. Previous diagnoses of IBS and depression are associated with delays in specialist review. Enhanced pathways are needed to accelerate specialist referral and timely IBD diagnosis.